2017
DOI: 10.1016/j.ymthe.2017.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Duvoglustat HCl Increases Systemic and Tissue Exposure of Active Acid α-Glucosidase in Pompe Patients Co-administered with Alglucosidase α

Abstract: Duvoglustat HCl (AT2220, 1-deoxynojirimycin) is an investigational pharmacological chaperone for the treatment of acid α-glucosidase (GAA) deficiency, which leads to the lysosomal storage disorder Pompe disease, which is characterized by progressive accumulation of lysosomal glycogen primarily in heart and skeletal muscles. The current standard of care is enzyme replacement therapy with recombinant human GAA (alglucosidase alfa [AA], Genzyme). Based on preclinical data, oral co-administration of duvoglustat HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…25 A recent short-term study with a pharmacologic chaperone plus ERT increased GAA activity in muscle without lowering glycogen content in patients with LOPD, demonstrating the need for a sustained effect to achieve biochemical correction. 26 Therefore, this is the first study to demonstrate improved biochemical correction of skeletal muscle in patients with LOPD who were previously treated with ERT. Improved biochemical correction supported our hypothesis that clenbuterol would increase CI-MPR-mediated uptake of GAA, since patients were stably treated and no greater biochemical correction was expected following >3 years of ERT.…”
Section: Discussionmentioning
confidence: 78%
“…25 A recent short-term study with a pharmacologic chaperone plus ERT increased GAA activity in muscle without lowering glycogen content in patients with LOPD, demonstrating the need for a sustained effect to achieve biochemical correction. 26 Therefore, this is the first study to demonstrate improved biochemical correction of skeletal muscle in patients with LOPD who were previously treated with ERT. Improved biochemical correction supported our hypothesis that clenbuterol would increase CI-MPR-mediated uptake of GAA, since patients were stably treated and no greater biochemical correction was expected following >3 years of ERT.…”
Section: Discussionmentioning
confidence: 78%
“…From early characterization of the catalytic site of GAA 25 and by homology with mechanistically dissected members of family GH31 26 , 27 , the catalytic nucleophile and acid/base can be assigned to D518 and D616, respectively. To get insight into the interaction of rhGAA with the documented pharmacological chaperone 1-deoxynojirimycin 16 , 28 and its derivative N-hydroxyethyl-deoxynojirimycin 29 (DNJ and NHE-DNJ, respectively), we soaked rhGAA crystals with these active site directed iminosugar inhibitors and obtained for both complexes diffraction data extending to 2.0 Å resolution (Table 1 ). DNJ binds in a 4 C 1 conformation in the substrate-binding subsite −1 30 and is stabilized by hydrogen bonds to the side-chains of D404, D518, R600, D616, and H674.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years PCT, presenting advantages such as low cost and burden, and high distribution volume, has emerged as an attractive alternative, either alone or in combination with ERT, for the treatment of LSDs 14 , 34 . For Pompe disease, for which clinical trials combining ERT and treatment with NB-DNJ and DNJ have recently been concluded 28 , 35 , PCT is particularly promising as pharmacological chaperones are small molecules that are expected to penetrate membranes and reach therapeutic levels in target tissues, including skeletal muscle (38–55% of human body weight), more easily than rhGAA. A potential drawback of most pharmacological chaperones under study for the rescue of lysosomal glycosidases is that they are active site-directed iminosugars and inhibitors of the target enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…By co‐administration of alglucosidase alfa with duvoglustat, the α ‐glucosidase enzyme activity and protein in plasma increased about twofold compared with ERT alone. In general, duvoglustat was well tolerated, without drug‐related adverse events …”
Section: Chaperone Therapymentioning
confidence: 93%